KOMPOSISI VEGETASI PENYUSUN TEMBAWANG SUTIAN DAN TEMBAWANG SUALAM DI KECAMATAN MANDOR KABUPATEN LANDAK - Ikwiras, .; Ekamawanti, Hanna Artuti; Widiastuti, Tri (JURNAL HUTAN LESTARI, 2016)
Tembawang is a system of land use by the Dayak community in West Kalimantan which is considered as a unique ecosystem for storing very high value. Overall, tembawang has three (3) values, namely the economic, the ecological, and socio-cultural values. This study aimed to obtain information tembawang Sutian vegetation composition and tembawang Sualam in District Overseer Porcupine District as well as knowing the dominant vegetation. The method used in this research is the analysis of vegetation in census measurement path way. Each transect made a plot with a size of 20 m x 20 m for the tree level, 10 m x 10 m for poles, 5 m x 5 m for saplings and 2 m x 2 m to the seedling stage. Research in tembawang hamlet village Sualam Ngarak districts Porcupine district foreman found at least 58 plant species from 19 families are different. Based on the analysis of the Shannon diversity index, tembawang Sutian at all stages of growth is relatively low species diversity index (H '<1), whereas in tembawang Sualam for all phases of growth indices were moderate abundant species diversity (1≤ H' ≤ 3), but different with pole phase where the index is relatively low species diversity (H '<1). While the dominance index analysis results both on tembawang Sutian and tembawang Sualam both dominance by rubber tree (family Euphorbiaceae). Keywords :       Tembawang , vegetation composition, species diversity , and the dominant species .